Concurrent cardiac sarcoidosis and obstructive sleep apnea presenting as arrhythmias - Malli, Foteini (BMC Pulm Med, 2020)
BACKGROUND: Cardiac involvement is a rare and potentially fatal presentation of sarcoidosis. Obstructive sleep apnea may complicate sarcoidosis. CASE PRESENTATION: We report a case of a sarcoidosis patient with cardiac involvement presenting with ventricular arrhythmias. Besides medical and invasive measures of therapy, the patient failed to respond fully. The patient was subjected to overnight polysomnography and diagnosed with concurrent obstructive sleep apnea syndrome. Following continuous positive airway pressure therapy, we observed a significant improvement of ventricular arrhythmias while methylprednisolone was further tapered. CONCLUSIONS: To our knowledge, this is the first report of cardiac sarcoidosis further implicated by OSAHS and presenting as ventricular arrhythmias that underlies the need for extensive testing in cardiac sarcoidosis in patients not responding to immunosuppressive therapy.